Some issues of the history of the establishment and perspectives of the development of theoretical and clinical medicine - Zamorskyi , I.I.; Khmara , T.V.; Biryuk , I.G.; Pankiv , T.V.; Koval , O.A. (Морфологія / Morphologia / Morfologìâ, 2024)
In recent decades, there has been a significant breakthrough in studying the embryonic and fetal periods of human development. This achievement was made possible by introducing the latest technologies, such as ultrasound scanners, computer tomography, and genetic analysis methods. Advanced capabilities of biochemical and cytogenetic analysis make it possible to study the development of the fetus in more detail, detect abnormalities in the formation of organs, and respond to possible pathologies in time, which opens new horizons for fetal surgery and perinatal medicine. Thanks to the technologies of prenatal diagnosis, the fetus is now considered a separate patient that needs special care and intervention when pathologies are detected. For example, ultrasound diagnostics in the early stages of pregnancy make it possible to detect structural defects, such as heart defects, as well as other abnormalities that occur during critical phases of development. Modern methods, including biochemical and molecular screenings, allow the identification of potential risks to the fetus’s health, such as genetic mutations or chromosomal abnormalities. Critical periods of fetal development, such as organogenesis, are key to the formation of major body systems. At this time, the most serious deviations are possible, which can lead to congenital malformations. Each organ system has its critical phases of development, and violations at this time can have irreversible consequences. According to estimates, congenital malformations consistently account for 3-4 cases per 1,000 births and are the cause of perinatal losses in 20-25% of cases. This emphasizes the importance of early diagnosis and timely intervention. Fetal surgery opens up new possibilities for the treatment of congenital anomalies even before birth. This includes procedures such as the correction of spinal hernias or diaphragmatic hernias. Early intervention improves the prognosis for the fetus and reduces risks for the mother. Thus, the development of modern technologies has significantly increased the possibilities of prenatal diagnosis and therapy, which opens new perspectives in pregnancy management and fetal care.